INTERNATIONAL COLLABORATION: UMJ and UTM TEACHING PRACTICE PERSPECTIVES - Iswan Iswan; Aswir Aswir (Universitas Muhammadiyah Semarang, 2018)
This paper reports on an international collaboration between two universities, one private university in Indonesia (Universitas Muhammadiyah Jakarta, UMJ) and one public and world class university in Malaysia (Universiti Teknologi Malaysia, UTM). Both collaborative action plans were implemented through projects in program development, faculty exchange, graduate student/teacher field experiences, pre-service student’s internship mentoring and also conjoined research in the area of a foreign/second language teaching and teacher development, and educational technology. Over a three-year period from 2015-2018 reported that UMJ, i.e Fakultas Ilmu Pendidikan (Faculty of Education) sent students for teaching practice to Fakulti Pendidikan UTM in four batches with 65 preservice students. In March 2018, UTM sent seven students to do internship program atUMJ. This collaboration commitment portrayed a smooth international partnership between universities and hoped to be continued in other field of collaborations. Keywords: international collaboration, teaching practice program, UTM, UMJ